INFLUENCIA DE LA "MANCHA AMARILLA" SOBRE LA COMPOSICIÓN QUÍMICA DEL CORCHO Y LA PRESENCIA DE TCA - García Vallejo, M. C.; Varea, S.; Cadahia, E.; Fernández de Simón, B. (III Congreso Forestal Español, 2001)
The anomaly of cork known as "yellow stain" has been considered as the main responsible for the presence, in some cork stoppers, of 2,4,6-trichloroanisole (TCA), compound that confers the "cork taint" to wine. In this Communication, a comparative study on the chemical composition of cork (suberin, waxes, polyphenols, holocellulose and lignin) and on the presence of chloroanisoles and chlorophenols is carried out with samples of healthy cork and cork affected with that anomaly. The cork with "yellow stain" differed from the healthy cork because of the presence of TCA and the low content of tannins.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español issue: 1995 pub-location: Granada
Keywords: chemical composition; Cork; yellow stain